Performance of the innovation-passion model for post Covid-19 - RITWATTHANAVANICH, N.; BENJAWAN, K.; PAVAPANUNKUL, S. (Utopía y Praxis Latinoamericana, 2021)
ABSTRACT Appealing to the concept of innovative financing, entrepreneurs refer themselves as the new normal entrepreneurs. Relatively, literature was the key creation of this study which indicated 1) perceived service quality 2) ROI-Return on Investment with customer retention and passion, and IROI-Innovative Return on Investment with dollars or baths entrepreneurs 3) managing the people side of innovation with links to the rules of engagement for minds and hearts and 4) authenticity. Respectively, for the synthesized review and production of this study, results revealed that the keywords of the authenticity of the innovation-passion model were 4 Ps: perception, purpose, preference, and profits. RESUMEN Apelando al concepto de financiación innovadora, los empresarios se refieren como nuevos empresarios normales. Relativamente, se estudió la literatura sobre la creación clave de este estudio en la que se indicaron 1) calidad de servicio percibida 2) Retorno de la Inversión con Retención (ROI) y pasión del cliente, e IROI-Retorno de la inversión innovador con los emprendedores de dólares o baños 3) Manejo del lado de las personas innovadoras con vínculos a las reglas de participación para involucrar mentes y corazones y 4) autenticidad. Respectivamente, para la revisión sintetizada y la producción de este estudio, los resultados revelaron que las palabras clave de la autenticidad del modelo pasión- innovación fueron 4 P, por sus siglas en ingles: percepción, propósito, preferencia y ganancias.